Antibiotic susceptibility patterns, biofilm formation and esp gene among clinical enterococci: is there any association? - Weng, Poh Leng; Ramli, Ramliza; Awang Hamat, Rukman (MDPI, 2019)
Enterococci are commonly found in humans, animals and environments. Their highly adaptive mechanisms are related to several virulent determinants and their ability to resist antibiotics. Data on the relationship between the esp gene, biofilm formation and antibiotic susceptibility profiles may differ between countries. This cross-sectional study was conducted to determine the proportion of esp gene and biofilm formation among Enterococcus faecalis and Enterococcus faecium clinical isolates. We also investigated the possible association between the esp gene with antibiotic susceptibility patterns and biofilm formation. The isolates were collected from clinical samples and identified using biochemical tests and 16SRNA. Antibiotic susceptibility patterns and a biofilm assay were conducted according to the established guidelines. Molecular detection by PCR was used to identify the esp gene using established primers. In total, 52 and 28 of E. faecalis and E. faecium were identified, respectively. E. faecium exhibited higher resistance rates compared to E. faecalis as follows: piperacillin/tazobactam (100% versus 1.9%), ampicillin (92.8% versus 1.9%), high-level gentamicin resistance (HLGR) (89.3% versus 25.0%) and penicillin (82.1% versus 7.7%). E. faecium produced more biofilms than E. faecalis (59.3% versus 49.0%). E. faecium acquired the esp gene more frequently than E. faecalis (78.6% versus 46.2%). Interestingly, the associations between ampicillin and tazobactam/piperacillin resistance with the esp gene were statistically significant (X2 = 4.581, p = 0.027; and X2 = 6.276, p = 0.012, respectively). Our results demonstrate that E. faecium exhibits high rates of antimicrobial resistance, esp gene acquisition and biofilm formation. These peculiar traits of E. faecium may have implications for the management of enterococcal infections in hospitals. Thus, concerted efforts by all parties in establishing appropriate treatment and effective control measures are warranted in future.